The labor market in the US, 2000-2018 - Daniel S. Hamermesh (IZA World of Labor, 2019)
As the largest economy in the world, the US labor market is crucial to the economic well-being of citizens worldwide as well, of course, that of its own citizens. Since 2000 the US labor market has undergone substantial changes, both reflecting the Great Recession, but also resulting from some striking trends. Most interesting have been a remarkable drop in the labor force participation rate, reversing a nearly 50-year trend; the full recovery of unemployment from the depths of the Great Recession; and the little-known continuing growth in post-inflation average earnings.
Keywords: E24; N32; 330; unemployment; real earnings; US